IRAN’S CULTURAL FOREIGN POLICY IN CENTRAL ASIA AND THE SOUTHERN CAUCASUS SINCE 1991 - JOHNSTON, William (CENTRAL ASIA AND THE CAUCASUS, 2007)
Although many foreign policy strategists put Iran’s cultural policy on the forefront of its foreign policy agenda, in Central Asia and the Southern Caucasus the Islamic Republic’s emphasis on culture is diminished when compared with its security and economic foreign policies.1 Iran’s foreign policy today is shaped more by pragmatism and realpolitik than it is by revolutionary Islam and a desire to export the revolution. Tehran’s reasons for pursuing a foreign policy that relies more on pragmatism than ideology are many. The Islamic Republic’s current foreign pol-icy objectives were molded significantly by its experiences with incorporating religious ideology into its foreign policy soon after the Islamic Revolution. A strong and coherent culturally emphasized foreign policy based on Revolutionary Is-lam as a prime motivator for geopolitical decision making was emphasized by Ayatollah Ruhollah Khomeini. The influence of the Islamic Revolution in Iran clearly had a profound impact on Iran’s foreign policy objectives. As such, in its early days the Islamic Republic of Iran attempted to spread the Islamic Revolution beyond its borders into the Muslim countries of the Persian Gulf.2 However, the Islamic Revolution was not accepted by Iran’s Persian Gulf neighbors, who instead felt an existential threat on their security made by Tehran’s brand of Islam. This threat was part of Saddam Hussein’s reasoning for attacking the Islamic Republic in the Iran-Iraq War of 1980-1988. The war had a significant impact on Iran’s domestic capabilities to provide both a sense of security as well as economic stability for its citizens. The impact of the conflict shifted Iranian thinking away from Islamic ideology and toward a foreign policy that focused on realpolitik and pragmatism. As Iran was isolated geopolitically and devoid of any influence outside the circles that supported Revolutionary Islam, the Islamic Re-public was forced to reorient its foreign policy to meet its security and economic needs. Thus, when the Soviet Union disintegrated in 1991, a cultural foreign policy was not at the top of Iran’s agenda in the new former Soviet south. Nor was the environment ripe for an export of the Islamic Revolution in the former Soviet re-publics. Islam had developed quite differently under the tutelage of the Soviet Union than it had developed in Iran. Soviet leaders emphasized nationalism and an overarching Soviet culture that naturally included use of the Russian language and state-sponsored atheism. Religion was not dis-mantled totally by the Soviets in the Central Asia and the Southern Caucasus, but it remained in place largely as a tool of nationalism rather than as a means of expression of piety. The cultural impact of the Soviet Union on these countries was not limited to Islam, and the need for cultural influence came soon after in-dependence. For the countries of Central Asia nationalism was only wrought under the watchful eye of the Supreme Soviet in Moscow, while it flourished in Georgia and Armenia centuries prior to Soviet occupation. It was the Central Asian countries, therefore, that subscribed the most to the Soviet-influenced nationalism; independence brought the overarching Soviet nationalism in these countries to an end and opened the door to allow for cultural influence from countries like Iran. Iran’s lack of use of revolutionary Islam as a cultural policy in Central Asia and the South-ern Caucasus thus stems from these two historical precedents: the lack of success in exporting the Islamic Revolution to Persian Gulf countries, and the legacy of the development of Islam under the Soviet Union. Iran’s non-pursuit of the export of the Revolution is realpolitik at its finest. Tehran now views promotion of revolutionary Islam out-side its borders as potentially destabilizing for the Islamic Republic in terms of both security and economy. Furthermore, the former Soviet republics are wary of Revolutionary Islam due to the nature of the development of Islam under the Soviet Union. In addition, Iran must check its own foreign policy desires in the context of Russia’s foreign policy needs. Iran’s restraint in exporting the Islamic Revolution is best characterized in the example of Tajikistan, where the political atmosphere was the most likely to accept an export of radical Islam. Iran could have supported the Islamist Coalition that was in power in Tajikistan, but instead chose to support the Russian-backed ex-communists. Tehran’s tools for cultural foreign policy are not limited to revolutionary Islam and ideology,